Penerapan Metode Skoring Untuk Penilain Hasil Belajar Siswa Di SDN Pondok Kelor II - ., Ryzca Siti Qomariyah; ., Maulitha Yuraida Rachman; ., Rizqiyanti Nur Karimah; ., Muhammad Syaiful Hilal (CV. ITTC INDONESIA, 2022)
Scoring and scoring systems are fundamental methods in the field of education, especially in Indonesia, because the results of scoring and scoring systems can measure students' abilities, learning attitudes, and learning outcomes within a certain period of time for basic considerations and to determine children's performance. . This article explains in detail about scoring and assessment systems in education.